(untitled) (Orfeu, 2025)
Music can be considered an element of social representation, which reflects the cultural identity of groups through the expression of their experiences and values. Therefore, music is often used as a means of resistance and representation, which also happened in the countryside. After their way of life changed due to agricultural modernization, rural people tend to resist in their places of origin. That being said, this paper aims to analyze rural people’s cultural identity representation based on country music and how it represents two different classes from the agrarian space: on one hand, there are the landowners’ descendants; on the other hand, the owners of small rural properties that make a living by running a family farm. This study is based on theoretical framework about cultural identity, agrarian space and music, as well as on country song lyrics analyses. The results suggest that music can be considered a political element, especially when it comes to representation, highlighting the contrast between styles and linked social groups.